1983
DOI: 10.1136/bmj.286.6360.207
|View full text |Cite
|
Sign up to set email alerts
|

Leg ulcers that do not heal.

Abstract: practice; all branches of pathology except haematology; radiology; radiotherapy and oncology; ear, nose, and throat surgery; ophthalmology; clinical pharmacology; and others. Service in one or other of these would often be more socially valuable than attempting to struggle into the ranks of general physicians, surgeons, and obstetricians and gynaecologists, where competition may be unnecessarily fierce and unrewarding. Satisfying and valuable careers are to be had in all of these shortage specialties. They are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Tissue biopsy is the gold standard for diagnosis of cutaneous malignancy. Ackroyd and Young recommend performing a biopsy if a chronic wound failed to respond satisfactorily after 3 months of reasonable treatment, whereas Hansson and Andersson recommend waiting for 4 months . In our experience, any sudden and suspicious change in the characteristics of a chronic wound should prompt the suspicion of a malignant transformation and biopsy is the only diagnostic test.…”
Section: Discussionmentioning
confidence: 85%
“…Tissue biopsy is the gold standard for diagnosis of cutaneous malignancy. Ackroyd and Young recommend performing a biopsy if a chronic wound failed to respond satisfactorily after 3 months of reasonable treatment, whereas Hansson and Andersson recommend waiting for 4 months . In our experience, any sudden and suspicious change in the characteristics of a chronic wound should prompt the suspicion of a malignant transformation and biopsy is the only diagnostic test.…”
Section: Discussionmentioning
confidence: 85%
“…For example, some authors have suggested that all ulcers that do not heal in four months should be biopsied to rule out the possibility of malignancy. 5 The results of our study suggest that such a criteria would result in three quarters of all chronic leg ulcers being biopsied.…”
Section: Introductionmentioning
confidence: 80%
“…There are no studies focused primarily on the safety of performing wound biopsies in chronic wounds. However, several practice guidelines have recommended performing wound biopsies for histological diagnosis or microbiologic testing in wounds that have not improved within 2–6 weeks of appropriate management 16–23 . The Food and Drug Administration (FDA) recommends performing biopsies of the wound, when needed clinically, as an objective tool to exclude neoplastic, immune‐mediated or primary infectious disease.…”
Section: Discussionmentioning
confidence: 99%